Reappraisal of the Subtropical Guidelines on Palivizumab Prophylaxis in Congenital Heart Disease - Chiu, Shuenn-Nan; Wang, Ching-Chia; Lin, Ming-Tai; Chen, Chun-An; Lu, Chun-Wei; Hua, Yu-Chuan; Wu, Jing-Ming; Wu, Mei-Hwan; Wang, Jou-Kou (Frontiers in Pediatrics, 2022)
Objective To define the impact of associated abnormalities on the efficacy of the novel subtropical guidelines for palivizumab prophylaxis on respiratory syncytial virus (RSV)-related hospitalizations in patients with hemodynamically significant congenital heart disease (hsCHD). Method This study enrolled every patient seen at a tertiary care center for hsCHD, who were born between 2014 and 2018 and received at least 1 dose of palivizumab, according to the subtropical guidelines. The patients were followed until the age of 2 years. Results A total of 772 patients (49% male) were enrolled. Cyanotic CHD was seen in 46% of patients, of whom 23% had associated abnormalities. Lung/airway abnormalities (14%) were the most common followed by the genetic syndromes associated with CHD (7.3%). Among the 772 patients, RSV-related hospitalizations occurred in 3.2% and 2.2% of whom aged ≤ 12 and 13-24 months, respectively. Most of the RSV infections occurred in patients not satisfying the criteria for palivizumab prophylaxis. The patients with associated abnormalities but not the type of CHD, patient age, and patient sex were risk factors for RSV-related hospitalizations. The rates of RSV-related hospitalizations, admission to the intensive care unit, and endotracheal intubation were higher for patients with associated anomalies than for other patients. Conclusion In agreement with the subtropical guidelines on palivizumab prophylaxis for patients with hsCHD, patients with associated abnormalities, especially genetic syndromes associated with CHD and lung/airway abnormalities, were at high risk of RSV-related hospitalizations.